New place of Centaurea borjae Valdés-Bermejo & Rivas Goday - Soñora, Francisco Xavier (Lazaroa, 2014)
In this work a new place is added about an important microendemism of Nothern Galaico-Asturian Subsector (Galaico-Asturian Sector) and localiced on a ground of granitic nature, which was considered until now as an endemic to ultrabasic rocks.